Evaluation of a new, low-dose levonorgestrel intrauterine contraceptive system over 5 years of use. (March 2017) - Gemzell-Danielsson, Kristina; Apter, Dan; Dermout, Sylvia; Faustmann, Thomas; Rosen, Kimberly; Schmelter, Thomas; Merz, Martin; Nelson, Anita
Abstract: Objective: To evaluate the efficacy and safety of a new, low-dose levonorgestrel intrauterine contraceptive system (LNG-IUS 12) for up to 5 years of use. Study design: In this Phase III study, 2885 nulliparous and parous women aged 18–35 years were randomized to LNG‐IUS 8 or LNG-IUS 12 for 3 years. After 3 years, women using LNG-IUS 12 could continue for up to 2 additional years (5 years total). The primary outcome was occurrence of pregnancy (Pearl Index). Secondary outcomes included safety, bleeding, dysmenorrhea, discontinuations, and user satisfaction. Results: From August 2007 through May 2008, out of 2885 women who were enrolled, 1453 were randomized to LNG-IUS 12. Placement was attempted in 1452/1453 (full analysis set). Mean age at baseline was 27.1 years; 39.5% were nulliparous. The cumulative 5-year Pearl Index (PI) was 0.29; the 5-year cumulative failure rate was 1.4%. The 5-year PI for ectopic pregnancy was 0.18. Over 5 years, 55.3% of women reported study drug-related treatment-emergent adverse events (TEAEs). Crude incidences of pelvic inflammatory disease, uterine perforation, and complete/partial LNG-IUS 12 expulsion were 0.6%, 0.2%, and 3.7%, respectively. Women using LNG-IUS 12 generally experienced less frequent bleeding over time. The incidence of amenorrhea during the last 90-day reference interval (end of Year 5) was 22.6%. Overall, 870 (59.9%) and 550 (37.9%) women completed 3 and 5 years of treatment, respectively; 77.8% of women who entered the extension phase completed 5 years of use. Over 5 years, 22.6% discontinued due to TEAEs, including 13 women who discontinued due to pregnancy; 76 discontinued due to bleeding problems including amenorrhea; and 163 discontinued due to desire for pregnancy, 71.2% of whom conceived within 12 months. Conclusion: In this study including parous and nulliparous women, LNG-IUS 12 was highly effective over 5 years of use and associated with a favorable safety profile. LNG‐IUS 12 offers women a low-dose contraceptive option for up to 5 years.